충청남도 보건소 간호사의 간호정보역량 실태 - 김현(Hyun Kim); 김미영(Mi Young Kim) (지역사회간호학회지, 2013)
Purpose: The aim of the study was to identify nursing informatics competencies of nurses working for public health centers in Chungcheongnam-do. Methods: Data were collected from June 10 to July 25, 2012 using the Nursing Informatics Competencies Questionnaire (NICQ). Data were analyzed by descriptive statistics, t-test, $x^2$-test, ANOVA and Pearson's correlation coefficient. Results: Nursing informatics competencies of the subjects showed a mean score of $3.3{±}1.0$ out of 5. As for scores of individual categories, the score for computer skills competencies was $3.3{±}1.0$, informatics knowledge competencies $3.4{±}0.9$, and informatics skills competencies $3.0{±}0.9$. Nursing informatics competencies were positively correlated with the subjects' ages (r=.65, p<.001), computer usage hours (r=.23, p = .015), levels of demand for informatics knowledge (r=.51, p<.001), and informatics skills education (r=.78, p<.001). Conclusion: Nursing informatics is required to be connected with job training or in-service education on account of its growing necessity for public health nurses. It is also essential to develop programs for strengthening informatics competencies reflecting sub-categories of educational needs.